SAÚDE MENTAL EM SALA DE AULA: A PERCEPÇÃO DE PROFESSORES UNIVERSITÁRIOS - Grecchi, Denilson (2009)
This dissertation deals with the perception of academics about Mental Health in the context of the classroom. The general objective of this study is to understand as the academical teachers discerns and struggles with their mental health and the one of their students in classroom. The author uses the interviews of 11 teachers of first and second semesters of the courses of the physiotherapy, journalism and systems of information of the Methodist University of São Paulo - UMESP. With base in Ground Theory method, the codes are accomplished opened, axial and selective of the data that they are contained in nine categories by end, being those: perception of the teachers' mental health; perception of the students' mental health; I handle of the teacher's mental health; I handle of the students' mental health; concept of health; concept of promotion of the health; contexts promoters of the health; contexts no promoters of the health and generating students' of discomfort handling. The central phenomenon gotten up starting from the data observed indicates a lonely practice, where the teacher just considers their psychological resources, their values and personal faiths as instruments to work with the emerging adversities in classroom. It is also observed a super valorization of the expository class and of the culture of giving class, practices that you/they don't stimulate a participation more democratic, autonomous and active on the part of the students. In that it adapts, the student appears as the largest problem to the educational practice, in the measure in that with his/her immaturity and inherent conflicts the adolescence doesn't allow the teacher to transmit the planned contents being this reason of frustrations and demotivation in the work. The lack of an institutional space where the teachers can change experiences, to expose their anguishes and to look for psychological support denounce the teachers' of the other instances of the institution estrangement. The classroom is not also noticed by the teachers as a possible space for the promotion of the health, being this understood more as a discipline than a group of actions and susceptible to practices be applied and motivated in classroom.(AU)